Numerical Concepts in Early Education: an ethnographic research - Maria Teresa Telles Ribeiro Senna; Beatriz Vargas Dorneles; Maria Angela Mattar Yunes (Universidade Federal do Rio Grande do Sul, 2013)
This paper describes a research that analyzed the early construction of number concepts in two to five year old children of Early Education. The qualitative ethnographic research was conducted in two schools: at the Núcleo de Desenvolvimento Infantil, Universidade Federal de Santa Catarina in Brazil and at the Scuola XXV Aprile, in Reggio Emilia, Italy. The aim was to describe the way that the spontaneous situations of number concepts were improved by teachers of these schools. In both schools the children demonstrated spontaneous opportunities of numerical constructions.The refore, those situations were not used by teachers to improve the children's numerical knowledge.